Structures, g‐tensors, and hyperfine coupling constants of L‐α‐alanine radicals in radiation dosimetry: An ab initio molecular dynamics simulation study. Issue 12 (25th March 2020) - Janbazi, Mehdi; Azar, Yavar T.; Ziaie, Farhood; Ghandi, Khashayar; Matta, Chérif F.; Shadman Lakmehsari, Muhammad
Abstract: Alanine is used as a transfer standard dosimeter for gamma ray and electron beam calibration. An important factor affecting its dosimetric response is humidity which can lead to errors in absorbed dose calculations. Ab initio molecular dynamics calculations were performed to determine the environmental effects on the electron paramagnetic resonance (EPR) parameters of L‐α‐alanine radicals in acidic and alkaline solutions. A new result, not dissimilar to the closed‐shell amino acid molecule alanine, is that the non‐zwitterionic form of the alanine radical is the stable form in the gas phase while the zwitterionic neutral alanine radical is not a stable structure in the gas phase. Geometric and EPR parameters of radicals in both gas and solution phases are found to be dependent on hydrogen bonding of water molecules with the polar groups and on dynamic solvation. Calculations on the optimized free radicals in the gas phase revealed that for the neutral radical, hydrogen bonding to water molecules drives a decrease in the magnitudes of g ‐tensor components g xx and g yy without affecting neither g zz component nor the hyperfine coupling constants (HFCCs). The transfer from the gas to solution phase of the alanine radical anion is accompanied with an increase in the spin density on the carboxylic group's oxygen atoms. However, for the neutral radical, this transfer from gas to solution phase is accompanied with the decrease in the spin density on oxygen atoms. Calculated isotropic HFCCs and g ‐tensor of all radicals are in good agreement with experiment in both acidic and alkaline solutions. Abstract : Solvation and pH effects on g ‐tensor and hyperfine coupling constants of L‐α‐Alanine radicals are elucidated by ab initio molecular dynamics simulations. The effects of humidity on electron paramagnetic resonance (EPR) parameters are quantified to elucidate the possible effects they have on radiation dosimetry using alanine. EPR parameters are found to be good diagnostics of hydrogen bonding with water of solvation.